Isolasi Protein Jewawut (Setaria Italica L) Dengan Metode Kjeldahl - Sumanto Pasally (Yayasan Literasi Sains Indonesia, 2022)
Consumption of staple foods of the community at this time depends on rice. Barley belongs to the cereal group which contains carbohydrates and protein which is not inferior to white rice or brown rice so that it has the potential to be applied to the food industry. Isolation of protein with pH variation to precipitate protein at its isoelectric point and observe the effect of pH on protein solubility. The Kjeldahl method is used to indirectly analyze crude protein levels in foodstuffs. Knowing the yield of protein isolate, N total protein before isolation and after isolation and crude fiber of barley seeds found in the Lambanan area, Balanipa District, Polman Regency, West Sulawesi. The research was carried out at the Makassar Health Center Laboratory and Post-Harvest Laboratories, Faculty of Agriculture, Indonesian Christian University, Toraja January – February 2022, the data obtained were presented in a quantitative descriptive manner by doing three replications. The highest protein isolate yield was at pH 12, which was 64.06%, the highest protein isolate content was at pH 11, which was 20.72%, and the crude fiber content of barley seeds was 1.51%.